Developing Skills for Youthful Leaders Module 2: Knowing and Accepting Yourself - Elizabeth B. Bolton; John R. Rutledge; Linda Bowman; Linda Barber (EDIS)
The objectives of this lesson are to increase self awareness, to recognize that each person is unique, to establish respect for names, and to develop a more positive attitude about oneself. This document is FCS9089, one of a series of the Family Youth and Community Sciences Department, UF/IFAS Extension. EDIS publication date May 2006.